2011
DOI: 10.1007/s00477-011-0527-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the spatial and temporal relationships between mosquito population dynamics and dengue outbreaks based on climatic factors

Abstract: Identifying the impact of climatic factors on mosquito population dynamics is of great importance for dengue outbreak control. The purpose of this study is to develop an approach to predict spatial/temporal mosquito reproduction and disease outbreaks. The prediction of a dengue outbreak is only possible if the temporal relationship between mosquito replication and the weather is known. At present, this is unclear and needs to be examined. Moreover, because the development of mosquito density is a dynamic proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Although various models have been proposed for the prediction of infectious disease spread, they mostly focus on long-term predictions that take into account explanatory variables, such as meteorological factors, to characterize the potential trend of the epidemic (Yu et al, 2011;Tu et al, 2012;Tsai et al, 2012). On the other hand, stochastic SIR models have been applied to simulate and predict the spatiotemporal diffusion of infectious diseases (Hufnagel et al, 2004;Cressie and Wikle, 2011;Ball and Sirl, 2012;Ji et al, 2012;de Souza et al, 2013;Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although various models have been proposed for the prediction of infectious disease spread, they mostly focus on long-term predictions that take into account explanatory variables, such as meteorological factors, to characterize the potential trend of the epidemic (Yu et al, 2011;Tu et al, 2012;Tsai et al, 2012). On the other hand, stochastic SIR models have been applied to simulate and predict the spatiotemporal diffusion of infectious diseases (Hufnagel et al, 2004;Cressie and Wikle, 2011;Ball and Sirl, 2012;Ji et al, 2012;de Souza et al, 2013;Zhang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…We have only considered Aedes aegypti here as they have very different ecological footprint compared to Aedes albopictus , hence they require different models. Furthermore, it has been shown that Aedes aegypti are the most competent vector for transmitting dengue, particularly in Taiwan [42]. For our study, we use the observed numbers of Aedes aegypti larvae and the number of observed containers (both inside and outside).…”
Section: Methodsmentioning
confidence: 99%
“…Tsai et al . [42] conclude that there may be a sharp inflation in the mosquito population, seven days after a period of intense rain, if the weather remains warm and humid. They also mention that this may not be an immediate impact of the rainfall, but its contribution to maintain humidity is preferred for larvae to survive.…”
Section: Introductionmentioning
confidence: 99%
“…The agent factor in the form of the dengue virus is transmitted through Aedes aegypti. Another factor had a big part in the environment, for example, geographical location, climatic and weather conditions in an area, which affects the increase of the spread pattern of DHF cases [9][10][11]. The trend of DHF cases generally occurs in the tropics and appears in the rainy season then decreases after the rainy season ends.…”
Section: Introductionmentioning
confidence: 99%